Formação da agenda para a ciência, tecnologia e inovação: um estudo multicaso em institutos federais no Rio Grande do Sul - Freitas, Rodrigo Uszacki Carvalho de (2021)
The objective of this research was to analyze the formation of the agenda related to ST&I in the Federal Institutes present in Rio Grande do Sul. It is a study of multiple cases where: the formation of the agenda for ST&I in the Federal Institutes analyzed; as a source of evidence documents, archival records and interviews; for data triangulation, Microsoft Excel® and NVIVO® software were used. In order to verify the theoretical trends on agenda formation, a Systematic Literature Review (RSL) was developed; in relation to the analysis of the agenda formation of the Federal Institutes, it was carried out through interviews and analysis of official documents. Regarding RSL, the sample comprised 116 studies from four databases: 9 from Scielo, 2 from Spell, 18 from Scopus and 87 from Web of Science. As main results, it is demonstrated that the multiple streams framework was applied in 27 studies. The punctuated equilibrium model (and its ramifications – Policy Agendas Project and Comparative Agendas Project), totaled 24 publications. It was observed that the agenda-setting theme evolves (from 1991 to 2012) from “emerging theme” to “motor/basic theme”, according to the classification proposed by Cobo et al. (2011). Regarding the agenda formation Institutes, the main emergencies demonstrate that the priorities established in the three bodies impact and contribute to: intelligent social and economic development; qualify and improve the management of the public agency; promote the capacity for innovation in the places where they are located; the development of basic and applied research. It was also observed that, within the scope of the three Institutes, the evidence indicates stability in the agenda formation, contrasting with a governmental agenda that is constantly receiving proposals for drastic changes, however, in the latter case, there has not yet been a coupling of streams so that these changes happen. In addition, the findings showed that the main actors in the agenda formation of these Institutes stand out: the students; campus directors; the members of the commissions that prepare the PDI; the members of the Superior Council; and the city halls.